Gênero e raça no trabalho em tecnologia da informação (TI) - Jordão Horta Nunes (Ciências Sociais Unisinos)
Information technology work includes occupations in which middle to high education prevails and which are developed in a heterogeneous field of economic activities. The article’s main objective is to analyze differences in terms of income and occupational insertion related to gender and race in the IT sector. The main data sources come from databases of the Brazilian government (Census, PNAD, RAIS), but also from academic production concerned with IT work, primarily in the sociology of work, economics and scientific policy issues. As regards gender, what was found was not exactly a pronounced difference in women’s and men’s average incomes, but a difference of inclusion in the occupational hierarchy, even with an inverted income gap in low level occupations. The professional identity in higher level occupations in the sector is guided by a valuing of risk and uncertainty, a trait traditionally associated with males by gender construction. As regards race, a negative income differential for black workers becomes evident. The Blinder-Oaxaca decomposition method applied to this differential reveals a residue indicating the existence of discriminatory relations in the IT sector, which range from education, age, tenure and occupational position to wage gaps.